Determining the impacts of climate change and urban expansion on terrestrial net primary production in China. (15th June 2019) - Wen, Youyue; Liu, Xiaoping; Bai, Yang; Sun, Yu; Yang, Jian; Lin, Kui; Pei, Fengsong; Yan, Yuchao
Abstract: Climate change and urbanization strongly affect the variations of terrestrial net primary production (NPP), but the relative contributions of these two factors to NPP changes have not been determined yet (especially on a macroscale). In this study, spatial-temporal variations of NPP in China from 2000 to 2010 were estimated using the Carnegie−Ames−Stanford Approach model, and the effects induced by urbanization and climate change were quantified. The obtained results showed that during the study period, the NPP in China exhibited an annual increase of 0.03 Pg C accompanied by large spatial heterogeneities. During the whole study period, the urban area in China increased by 16.44 × 10 3  km 2, and the corresponding NPP losses amounted to 11.60 × 10 −3  Pg C. Urban expansion significantly offset the climate change-induced NPP increases and worsened NPP decreases (the offsetting ratio calculated for China was 5.42%, and its exact magnitudes varied by province). The largest NPP variations were observed over the regions with rapid urban expansion, whose contribution ratio was 32.20% for China and exceeded 30% for most provinces. Climate change contributed considerably to the NPP variations in both the newly urbanized (30.45%) and purely vegetated (46.92%) areas, but its contribution ratios were slightly lower than those of residual factors. Moreover, climate change strongly affected the NPP levels over the arid and semi-arid regions as well as over the Tibet Plateau; however, residual factors dominated the NPP variations over the central and southeast China. Our study highlights a significant role of urbanization in driving terrestrial NPP variations on a macroscale and provides a new perspective on disentangling the impacts of external factors on NPP values. Highlights: Urbanization offsets 5.42% of climate-induced NPP increases at a country scale. Urbanization contributes 32.20% of NPP changes at whole China. NPP variations in high-speed urban sprawl areas were led by Urbanization. Climate change dominated the NPP variations in arid and semi-arid regions. Residual factors ran the NPP changes in central and southeast China predominantly.